Propolis as an Adjuvant in the Healing of Human Diabetic Foot Wounds Receiving Care in the Diagnostic and Treatment Centre from the Regional Hospital of Talca - Verónica Mujica; Roxana Orrego; Roberto Fuentealba; Elba Leiva; Jessica Zúñiga-Hernández (Journal of Diabetes Research)
Objective. Diabetic foot wounds are a relevant diabetes complication and a major health problem. It has been described that propolis has health benefits due to its anti-inflammatory, antioxidant, and support in the healing process. The current study assessed the effect of propolis as an adjuvant in the healing of human diabetic foot ulcers. This was evaluated in a randomized placebo-controlled study of subjects receiving care in the Diagnostic and Treatment Centre from the Regional Hospital of Talca, Chile. Research Design and Methods. Randomized subjects received ambulatory healing treatment for diabetes foot wounds with propolis spray (3%), which was applied to cover the entire wound surface each time it was dressed from week 0 until cicatrization or 8 weeks as a maximum. Two serum samples were taken (day 0 and end of the study) for cytokine and oxidative stress analyses. Also, macro- and microscopy were analyzed in the process of wound healing. Results. The study comprised 31 subjects with type 2 diabetes in treatment for diabetic foot wounds in the Diagnostic and Treatment Centre from the Regional Hospital of Talca. Propolis promotes a reduction of the wound’s area by an average of 4 cm2, related to an increase in the connective tissue deposit compared to the control. Also, propolis increased the glutathione (GSH) and GSH/glutathione disulfide (GSSG) ratio (p<0.02), depleted tumor necrosis factor- (TNF-) α, and increased interleukin- (IL-) 10 levels. Topical propolis did not modify the biochemical parameters in the serum of the studied subjects. Conclusions. The topical use of propolis turned out to be an interesting therapeutic strategy as an adjuvant in the care of diabetes foot wounds due to its ability to improve and promote healing based on its anti-inflammatory and antioxidant profile. This trial is registered with NCT03649243.